Neonatal and infant readmissions for late preterm and early term babies in Ontario and England: a cohort study using linked population-level healthcare data. (2017) - Harron, Katie; Gilbert, Ruth; Guttmann, Astrid; Cromwell, David; Meulen, Jan van der
No abstract available